Identificação da dinâmica espaço-temporal para estimar área cultivada de soja a partir de imagens MODIS no Rio Grande do Sul - Santos, Juliana S. Dos; Fontana, Denise C.; Silva, Thiago S. F. [UNESP]; Rudorff, Bernardo F. T. (Departamento de Engenharia Agrícola - UFCG, 2014)
The objective of this study was to define a method for estimating soybean crop area in the Northern Rio Grande do Sul state (Brazil). Overall, six different remote sensing methods were proposed based on spectral-temporal profile and minimum and maximum values of NDVI/MODIS related to the stages of sowing, maximum development and harvesting of soybean areas. The resulting estimates were compared to official crop area data provided by the Brazilian government, using statistical analysis and the fuzzy similarity method. The performance of each method depended on information such as crop size, type of crop management, and sowing/harvesting dates. Regression coefficients of determination and fuzzy agreement values were above 0.8 and 0.45, respectively, for all methods. For operational monitoring of soybean crop area, the empirical threshold applied to the image difference with inclusion of harvest image method was the most effective, producing estimates that matched closely the official data. For spatial analysis the application of multitemporal images classification method is recommended that generated a map of better quality. The efficiency of these methods should be evaluated in the areas of soybean expansion in the state.

Com este trabalho propõe-se definir um método para estimar a área cultivada de soja na região norte do Rio Grande do Sul. Foram propostos seis métodos baseados no perfil espectro-temporal e de valores mínimos e máximos de imagens NDVI/MODIS referentes às etapas de semeadura, máximo desenvolvimento e colheita das áreas de soja. As estimativas obtidas foram comparadas com dados oficiais do IBGE a partir de análises estatísticas e da análise espacial fuzzy. Os resultados indicaram que estimativas agrícolas satisfatórias são dependentes de características como o tamanho, o tipo de manejo e a época de plantio e de colheita das lavouras. Para todos os métodos avaliados foram obtidos valores de coeficientes de determinação e da análise fuzzy superiores a 0,8 e 0,45, respectivamente. O método limiar empírico aplicado à imagem diferença com inclusão do final de ciclo, gerou estimativas iguais às dos dados oficiais do IBGE, característica que ressalta a utilização deste método em programas operacionais de previsão de safras. Para análises espaciais recomenda-se a aplicação do método Classificação de imagens multitemporais que gerou um mapa de melhor qualidade. A eficiência dos métodos deve ser avaliada em áreas de expansão de soja no Estado.
Identification of the spatial and temporal dynamics for estimating soybean crop area from MODIS images in the Rio Grande do Sul, Brazil
Keywords: imagens multitemporais; fenologia; previsão de safras; sensoriamento remoto; multitemporal imagery; phenology; crop yield predictive; remote sensing